2014
DOI: 10.1007/s11832-014-0617-9
|View full text |Cite
|
Sign up to set email alerts
|

The acetabulum in Perthes’ disease: A prospective study of 123 children

Abstract: PurposeWe assessed the radiographic changes of the acetabulum during the course of Perthes’ disease and investigated whether they were associated with femoral head sphericity 5 years after diagnosis.MethodsWe studied 123 children with unilateral Perthes’ disease, femoral head necrosis more than 50 % and age at diagnosis 6 years or older. Pelvic radiographs were taken at onset, 1 year and 5 years after diagnosis. Sharp’s angle, acetabular depth-to-width ratio (ADR) and lateral acetabular inclination were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
2
15
0
4
Order By: Relevance
“…The decrease in coverage angle in those quadrants, in addition to the decrease in acetabular anteversion observed in this study, is consistent with previous publications on patients affected by LCPD . It is interesting to note that we did not find a significant difference in the acetabular radius nor in the total area of the acetabulum, which differs from previous clinical studies of patients with LCPD . This may be secondary to differences in measurement, as those studies relied on an AP pelvis radiograph, where in this case the measurement was made using three‐dimensional CT images.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The decrease in coverage angle in those quadrants, in addition to the decrease in acetabular anteversion observed in this study, is consistent with previous publications on patients affected by LCPD . It is interesting to note that we did not find a significant difference in the acetabular radius nor in the total area of the acetabulum, which differs from previous clinical studies of patients with LCPD . This may be secondary to differences in measurement, as those studies relied on an AP pelvis radiograph, where in this case the measurement was made using three‐dimensional CT images.…”
Section: Discussionsupporting
confidence: 91%
“…Much of the research on this topic has been focused on the changes to the femoral head, however, there are also changes that occur which affect the morphology of the acetabulum. Clinical studies examining radiographic changes to the acetabulum have shown articular hypertrophy in the superior and medial aspects of the acetabulum, upward sloping of the lateral margin of the acetabulum, as well as premature fusion of the triradiate cartilage . Subsequent studies have shown that patient's with LCPD were more likely to have acetabular retroversion, and be associated with anterolateral labrum and cartilage damage …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The average centre-to-centre distance was also significantly higher in LCP (of 3.0 ± 1.3 (SD) mm) when compared with 1.2 ± 0.5 (SD) mm in the normal side. In addition, Huhnstock et al (2014) analysed the changes in the acetabulum in children with unilateral LCP and observed that during the first year after the diagnosis. The acetabular depth-to-width ratio (ADR) decreased when compared with the normal hip, due to a decrease in depth of 10% and an increase in width of 10%.…”
Section: Introductionmentioning
confidence: 99%